Time‐Dependent Hybrid Plasma Simulations of Lunar Electromagnetic Induction in the Solar Wind. Issue 8 (17th April 2019) - Fuqua Haviland, H.; Poppe, A. R.; Fatemi, S.; Delory, G. T.; de Pater, I.
Abstract: Understanding the structure and composition of the lunar interior is fundamental to furthering our knowledge of the formation and subsequent evolution of the Earth‐Moon system. Among various methods, electromagnetic sounding is a valuable approach to constraining lunar interior structure. While Apollo‐era electromagnetic sounding analyses of lunar magnetometer observations reported constraints on the lunar interior structure, the presence of perturbing plasma currents and magnetic fields was often regarded as a second‐order correction. Here, we use AMITIS, a three‐dimensional, time‐dependent hybrid plasma model with a conducting lunar interior to demonstrate that electromagnetic fields from the lunar wake and from the lunar interior interact and thereby alter geophysically induced electromagnetic fields. Our results indicate that electromagnetic sounding of airless bodies interacting with a conductive plasma and exposed to a time‐varying magnetic field must be interpreted via plasma models in order to untangle plasma and induced field contributions. Plain Language Summary: Magnetic field observations near the Moon can be used to remotely detect the interior. These observations can be related back to composition, structure, and temperature. This technique was applied during Apollo using a surface magnetometer and in orbit. When the Moon is outside of the Earth's magnetic field, the lunar surface interacts directly with the solar wind plasma particles from the Sun. The Moon's presence interrupts this steady flow of plasma by absorbing particles on the sunlit side, while a region of no particles forms on the opposite side. This plasma wake generates its own magnetic fields that interact with interior fields. In order to understand any contribution to the observations, we apply a new computer simulation, which solves first principles equations to determine the plasma wake and interior fields in three dimensions and in time. This novel technique provides a new understanding of the Moon‐plasma magnetic field interaction and improves previous models that neglected this interaction. Previous interpretations assumed any interior fields on the nightside were trapped within the plasma wake cavity; however, we see these magnetic fields are coupled with the wake magnetic fields. This is applicable to any airless body in a similar space‐plasma environment. Key Points: A time‐dependent hybrid plasma model studies the interaction of induced magnetic fields and the lunar plasma environment Induced magnetic fields from the lunar interior self‐consistently couple with ambient plasma and thereby differ from analytic predictions Coupling of plasma interaction with induction must be accounted for in electromagnetic sounding studies of airless bodies